Independently controllable dual-band terahertz metamaterial absorber exploiting graphene. (12th April 2019) - Zhou, Qihui; Zha, Song; Bian, Li-an; Zhang, Jihong; Ding, Liang; Liu, Hanqing; Liu, Peiguo
Abstract: In this paper, we demonstrate the design and characterization of a controllable dual-band terahertz metamaterial absorber formed by cascading a Salisbury-screen-like structure based on patterned graphene and a gold-graphene hybrid frequency selective surface. By electrostatically changing the chemical potentials of the graphene layers, absorptivity and operating frequency of the metamaterial absorber can be tuned independently without interference. Simulations indicate the absorptivity of the first absorbing peak can be varied from 35% to greater than 99% at 1.45 THz while the position of the second one can be tuned from 2.85 THz to 3.6 THz continuously with absorptivity of 90%. It provides a new perspective on the design of multiband tunable absorbers, thus promoting the realization of terahertz sensors and detectors for practical applications.